Educational ecosystems: a research model applied in four Italian territories of the Tuscany Region - Giovanna Del Gobbo; Paolo Federighi; Francesco De Maria; Daniela Frison; Glenda Galeotti; Silvia Iossa; Giorgia Pasquali; Beatrice Spennato (Firenze University Press, 2022)
The article presents the OLESchool research, which conducted a feasibility study aimed at the definition of an integrated learning ecosystem model in which the school system becomes the focus of an open learning environment. The research considered the criticalities, priorities and limitations related to the pandemic event, highlighting the resources and opportunities generated, and aimed to identify those success factors and criteria for building prototypes and hypotheses of expected results to be implemented at a subsequent stage. The research adopted a collaborative approach starting with the stakeholder engagement process. The research team applied a methodological design inspired by the Grounded Theory paradigm, studying the phenomenon holistically from different points of view with qualitative-quantitative parallel research phases and triangulation between researchers, theories, data and tools. The contribution presents the results, distinguished between output and outcome of the research.   Ecosistemi educativi: un modello di ricerca applicato in quattro territori della Toscana. Il contributo presenta la ricerca OLESchool che ha visto la realizzazione di uno studio di fattibilità volto alla definizione di un modello di ecosistema formativo integrato dove il sistema scolastico diventa fulcro di un ambiente di apprendimento aperto. Sono state tenute in considerazione criticità, priorità e vincoli relativi all'evento pandemico, facendo emergere le risorse e le opportunità scaturite e puntando all'individuazione di quei fattori di successo e criteri di costruzione di prototipi e ipotesi di risultati attesi da implementare in una fase successiva. La ricerca ha seguito un approccio di tipo collaborativo a partire dal processo di stakeholder engagement. È stato adottato un disegno metodologico ispirato al paradigma della Grounded Theory, studiando il fenomeno in modo olistico da punti di vista differenti, con fasi di ricerca parallele quali-quantitative e trasversali di triangolazione tra ricercatori, teorie, dati e strumenti. Nel contributo sono presentati i risultati distinti tra output e outcome della ricerca.